2003
DOI: 10.1152/jn.00139.2003
|View full text |Cite
|
Sign up to set email alerts
|

Neural Changes in Cat Auditory Cortex After a Transient Pure-Tone Trauma

Abstract: Noreñ a, Arnaud J., Masahiko Tomita, and Jos J. Eggermont. Neural changes in cat auditory cortex after a transient pure-tone trauma. J Neurophysiol 90: 2387-2401, 2003. First published May 28, 2003 10.1152/jn.00139.2003. Here we present the changes in cortical activity occurring within a few hours after a 1-h exposure to a 120-dB SPL pure tone (5 or 6 kHz). The changes in primary auditory cortex of 16 ketamine-anesthetized cats were assessed by recording, with two 8-microelectrode arrays, from the same multiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
83
2
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(99 citation statements)
references
References 41 publications
12
83
2
2
Order By: Relevance
“…This is comparable to the change found by Noreñ a et al (2003), within a few hours after the noise trauma, in the CF range one octave above the trauma-tone frequency.…”
Section: Figsupporting
confidence: 85%
See 3 more Smart Citations
“…This is comparable to the change found by Noreñ a et al (2003), within a few hours after the noise trauma, in the CF range one octave above the trauma-tone frequency.…”
Section: Figsupporting
confidence: 85%
“…It was surprising that the noise-induced hearing loss was frequency-independent over a wide range, albeit there was about 10 dB more hearing loss in the 16-to 24-kHz range, as measured by ABR, and up to 20 dB more above 16 kHz as measured by multiunit thresholds in the cortex. This is different from that observed about 5 h after a noise trauma; here, the loss is negligible up to 4 kHz and then rapidly increases to about 40 dB for frequencies above 6 kHz (Noreñ a et al 2003;Tomita et al 2004). At longer times, after the trauma, the loss typically reduces somewhat but does not spread to frequencies below 4 kHz (Seki and Eggermont 2002;Noreñ a and Eggermont 2005).…”
Section: Figmentioning
confidence: 56%
See 2 more Smart Citations
“…Earlier studies demonstrated that cochlear injury can be generated by high intensity sound exposure (100-120 dB SPL). This damage is usually accompanied by elevated sound intensity thresholds (18)(19)(20)(21). It was recently shown that such noise-induced peripheral hearing loss also affects cortical tMTFs to amplitudemodulated noises in cats (22).…”
Section: Discussionmentioning
confidence: 99%